Qualitative Case Study Research in Education: A Systematic Review of Methodological Approaches and Analytical Practices - Ummu Khairiyah; Pance Mariati; Silviana Nur Faizah; Kiky Chandra Silvia; Febriarsita Eka Sasmita (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
This study examines methodological approaches and analytical practices in qualitative case study research within educational contexts. The increasing diversity in the interpretation and implementation of case study research has created methodological inconsistencies, particularly in research design, data collection, and data analysis procedures. Therefore, this systematic review aims to identify methodological characteristics, classify case study approaches, and analyze analytical practices employed in qualitative educational case study research. This study employed a systematic literature review guided by the PRISMA framework. Articles were retrieved from Scopus-indexed journals published between 2018 and 2023. The selected studies were analyzed based on research design, participant selection, data collection techniques, and data analysis procedures. The findings reveal that qualitative case study research in education predominantly employs semi-structured interviews, observations, and document analysis as primary data sources. Thematic analysis, coding procedures, and triangulation techniques were frequently used to enhance data validity and interpretation. The review also identified variations in the classification and implementation of intrinsic, instrumental, explanatory, and exploratory case studies. These findings highlight the importance of methodological rigor and conceptual clarity in conducting qualitative case study research in educational settings. Keywords: qualitative case study, educational research, systematic literature review, methodological approaches, analytical practices